Accounting Education Challenges in the New Millennium Era - Sofik Handoyo; Syaiful Anas (Universitas Padjadjaran, 2019)
The new Millennium era is closely associated with turbulence business environment along with advanced Information and technology. Job market demands university graduates to concern not only technical skills but also beyond that. Accounting education institutions must respond to the changes by providing education systems that comply with market expectations. This paper described critical thinking related new orientation of accounting education institutions in responding advanced of technology, dynamic business environment along with millennial generation characteristics. This paper explored using literature review perspective to understand the implications of advanced technology, changing the business environment, and the unique character of the millennial generation on accounting education in higher institutions. The paper is expected to give a new perspective for accounting education institutions in terms of handling education process in the era with full of technologically advanced, dynamic business environment and the different character of a student of the millennial generation. Accounting academicians need to adapt in terms of teaching method to fulfill market expectation towards accounting graduates. Accounting Education institutions must be aware of their system education, curriculum, and learning outcomes. This paper explores some ways in which this might be achieved and some of the challenges to effecting change in accounting education that will have to be overcome